Design approaches of performance-scaled rotor for wave basin model tests of floating wind turbines. (April 2020) - Wen, Binrong; Tian, Xinliang; Dong, Xingjian; Li, Zhanwei; Peng, Zhike; Zhang, Wenming; Wei, Kexiang
Abstract: The Froude scaling law is usually utilized in the wave basin model tests of Floating Wind Turbines (FWTs). However, the Froude-Scaled Rotor (FSR) cannot generate desired aerodynamic loads due to the Reynolds-Number Scaling Effect (RNSE). To mitigate the adverse effects of RNSE, two approaches are proposed to design Performance-Scaled Rotors (PSRs) in this paper. Taking DTU 10 MW baseline wind turbine as an example, the SD2030 airfoil is selected to replace the original FFA-W3-xx airfoils. Maximum Lift Tracking (MLT) and Load Distribution Matching (LDM) algorithms are proposed to assign the chord lengths and twist angles. Herein, MLT leads all airfoils to operate at the optimal angle of attack that corresponds to the maximum lift coefficient and afterwards increasing the chord lengths. LDM simultaneously adjusts the chord length and twist angle, aiming to match the span-wise distribution of normal force at the design point. Results show that both approaches can generate desired rotor thrusts in a range of tip speed ratios, which seems to outperform prior PSRs in the existing publications. The blade mass and inertia can be preserved with careful manufacturing procedures. The redesigned PSRs are helpful to improve the accuracy and reliability of FWT model tests in the wave basin. Highlights: Reynolds-Number Scaling Effect (RNSE) of model rotor in wave basin test is introduced. Potential approaches to mitigate the adverse of RNSE are analyzed in detail. MLT and LDM algorithms are proposed to redesign PSR for FWT wave basin tests. Two PSRs are designed for DTU 10 MW wind turbine based on MLT and LDM.